Pemberdayaan Anak-Anak TK dengan Pembelajaran Kosa kata & Numerasi Berbasis Fun Game dan Education - Ni Made Rianita (PT. Karya Inovatif Nusantara, 2024)
Many aspects of human life have changed due to advances in science and technology. Education is the key to the country’s future development and it starts from early childhood to adulthood. Therefore, changes and improvements continue to be made in various education sectors. In this case, the researcher wants to apply a learning media called